2001
DOI: 10.1063/1.1370997
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectra and structural phase transition in nanocrystalline lead lanthanum titanate

Abstract: The effects of particle size on the structure and Raman spectra of lead lanthanum titanate nanocrystalline particles are investigated. Samples with different particle sizes were prepared by the sol-gel process using different calcination temperatures. The sizes of the crystallites of particles were determined by x-ray diffraction with the aid of Scherrer's equation. Raman vibration modes of samples with various particle sizes were also studied by Raman scattering at room temperature. The results show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…No differences could be detected from the XRD patterns of the PLT compound calcined at a higher temperature. For the PLT compound calcined at different temperatures, both the Curie temperature and the tetragonality of the poorly crystallized grains become lower than those of the completely crystallized grains [12]. Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…No differences could be detected from the XRD patterns of the PLT compound calcined at a higher temperature. For the PLT compound calcined at different temperatures, both the Curie temperature and the tetragonality of the poorly crystallized grains become lower than those of the completely crystallized grains [12]. Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Glacial acetic acid (CH 3 COOH) was used as catalyst. The synthesis processes have been described in detail elsewhere [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The main factors that influence the dimension of the grains are the temperature and calcination time. The temperature should not exceed 600 • C and the calcination time should be the extremely short, no longer than half an hour [29][30][31]. 2.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Shiratori et al [27] observed a new metastable polymorph structure in KNaNb 2 O 6 when the grain size decreased below 200 nm. Furthermore, the phase transition temperature of BaTiO 3 was also proposed to be size dependent, similar to (Pb 0.9 La 0.1 )TiO 3 reported by Zhou et al [28,29]. As such, grain size of the KNNbased ceramics may also have some influences on the electrical properties.…”
Section: Introductionmentioning
confidence: 85%